1995
DOI: 10.1126/science.7652557
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Energy Homeostasis in C/EBPα Knockout Mice

Abstract: Mice homozygous for the targeted deletion of the c/ebp alpha gene, which expresses the CCAAT/enhancer-binding protein alpha (C/EBP alpha), did not store hepatic glycogen and died from hypoglycemia within 8 hours after birth. In these mutant mice, the amounts of glycogen synthase messenger RNA were 50 to 70 percent of normal and the transcriptional induction of the genes for two gluconeogenic enzymes, phosphoenolpyruvate carboxykinase and glucose-6-phosphatase, was delayed. The hepatocytes and adipocytes of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
648
3
10

Year Published

1998
1998
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 883 publications
(696 citation statements)
references
References 25 publications
29
648
3
10
Order By: Relevance
“…As FMIP influences myeloid differentiation as well, we examined the common key factors in both differentiation systems. One candidate is a protein belonging to the C/EBP family (Cao et al, 1991;Wang et al, 1995;Tenen et al, 1997;Lane et al, 1999), as it has been demonstrated that timely expression of C/ EBPalpha and C/EBPbeta is essential for adipocyte differentiation (Fux et al, 2004;Mori et al, 2005). Therefore, we examined the expression of C/EBPalpha and C/EBPbeta during differentiation in FMIP-overexpressing and knockdown cells.…”
Section: Fmip Influences the Expression Of C/ebpalpha Gene During Adimentioning
confidence: 99%
“…As FMIP influences myeloid differentiation as well, we examined the common key factors in both differentiation systems. One candidate is a protein belonging to the C/EBP family (Cao et al, 1991;Wang et al, 1995;Tenen et al, 1997;Lane et al, 1999), as it has been demonstrated that timely expression of C/ EBPalpha and C/EBPbeta is essential for adipocyte differentiation (Fux et al, 2004;Mori et al, 2005). Therefore, we examined the expression of C/EBPalpha and C/EBPbeta during differentiation in FMIP-overexpressing and knockdown cells.…”
Section: Fmip Influences the Expression Of C/ebpalpha Gene During Adimentioning
confidence: 99%
“…Members of the C/EBP family are known to have an essential role in adipose tissue development (Cao et al, 1991;Samuelsson et al, 1991;Umek et al, 1991;Freytag and Geddes, 1992;Wang et al, 1995;Yeh et al, 1995) and FUS-CHOP blocks di erentiation of adipogenic precursors in tissue culture (Kuroda et al, 1997;Adelmant et al, 1998). Whereas interference with the normal process of di erentiation may contribute to the oncogenic potential of FUS-CHOP fusion protein, it is a property that they share with the nontransforming germline CHOP gene product (Zinszner et al, 1994;Batchvarova et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Although tissue expression patterns of these members often overlap, recent studies using gene knockout analysis of C/EBPs in mice revealed that C/EBPs differ significantly in their physiological functions and in their downstream target genes. For example, mice lacking C/EBP␣ die shortly after birth due to severe hypoglycemia and the absence of glycogen storage in liver (23), whereas knockout of C/EBP␤ causes defects in female reproduction (18).…”
mentioning
confidence: 99%